Modeling airway persistent infection of Moraxella catarrhalis and nontypeable Haemophilus influenzae by using human in vitro models - Ariolli, Andrea; Canè, Martina; Di Fede, Martina; Tavarini, Simona; Taddei, Anna Rita; Buno, Kevin Pete; Delany, Isabel; Rossi Paccani, Silvia; Pezzicoli, Alfredo (Frontiers in Cellular and Infection Microbiology, 2024)
Non-typeable Haemophilus influenzae (NTHi) and Moraxella catarrhalis (Mcat) are two common respiratory tract pathogens often associated with acute exacerbations in Chronic Obstructive Pulmonary Disease (COPD) as well as with Otitis Mediaotitis media (OM) in children. Although there is evidence that these pathogens can adopt persistence mechanisms such as biofilm formation, the precise means through which they contribute to disease severity and chronicity remains incompletely understood, posing challenges for their effective eradication. The identification of potential vaccine candidates frequently entails the characterization of the host-pathogen interplay in vitroin vitro even though this approach is limited by the fact that conventional models do not permit long term bacterial infections (>48 hours). In the present work, by using air-liquid-interface (ALI) in vitroin vitro human airway models, we aimed to recreate in vitroin vitro COPD-related persistent bacterial infections. In particular, we explored an alternative use of the ALI system consisting in the assembly of an inverted epithelium grown on the basal part of a transwell membrane with the aim to enable the functionality of natural defense mechanisms such as mucociliary clearance and cellular extrusion that are usually hampered during conventional ALI infection experiments. The inversion of the epithelium did not affect tissue differentiation and considerably delayed NTHi or Mcat infection progression, allowing one to monitor the host-pathogen interactions for up to three weeks. Notably, the use of these models, coupled with confocal and transmission electron microscopy, revealed unique features associated with NTHi and Mcat infection in vitroin vitro, highlighting persistence strategies including the formation of intracellular bacterial communities (IBCs) and surfaceassociated biofilm-like structures. Overall, this study demonstrates the possibility to perform long term host-pathogen investigations in vitroin vitro with the aim to define persistence mechanisms adopted by respiratory pathogens and individuate potential new vaccine targets.